Love For All, Hatred For None: Narasi Kemanusiaan dan Primasi Perlawanan Stigma Jemaat Ahmadiyah Indonesia - Mardian Sulistyati (JURNAL INDO-ISLAMIKA, 2015)
The articles examines the primacy of the fighting of Indonesian Ahmadiyya community (JAI) against a stigma perspectively and contextually to join with the majority’s social system. The fieldwork took place in Kampung Gondrong Tangerang, Banten. The research shows that the resilience and power of JAI originate in love for all hatred for none principles which protect their existence in the face of threat and pressure. The article also proves that both the power and the resilience of JAI result from their awareness to strategically develop many ways to deal with the stigma. This is the jihad of JAI as a foundation to motivate the community and spread out their influences.